Религиозная лексика в современном русском и польском языках в переводоведческом, лексикографическом и лингвокультурологическом освещении : (на примере православного эортонима „Пасха”) - Gadomska, Halina (Theoria et Historia Scientiarum, 2024)
During the first quarter of the 21st century, Polish and Russian linguistics have been experiencing an intensification of research into the languages of various Christian denominations. In Poland, it is usually the language of the Polish Catholic Church, traditionally associated with the Polish language; in Russia, it is the language of the Russian Orthodox Church, speaking of which, Church Slavonic and Russian are usually meant. Due to the ongoing geopolitical processes, wellknown classical parallels or connections such as “Polish – Catholic”, “Russian – Orthodox” and directions of this kind of research are undergoing changes. In the Polish Orthodox Church, whose ministers and parishioners until recently used mainly Church Slavonic and Polish, today they increasingly turn to Russian, Belarusian, Ukrainian and other Slavic languages in their daily lives. Therefore, against the background of the predominance of Catholicism and the Polish language, problems arise with the correct interpretation and correct understanding of basic religious names by representatives of various Christian denominations speaking related Slavic languages. As a result, there are studies of parallels and connections such as “Polish, Russian, Ukrainian – Orthodox”, and questions arise, the answers to which can be tried to find in lexicography.